Analysis Of Accounting Fraud Tendencies At Village Credit Institutions In Gianyar Regency With Pentagon Fraud Approach - Ni Luh Putu Mita MIATI; I Nyoman SUTAPA (International Journal of Environmental, Sustainability, and Social Science, 2021)
Village credit institutions (Village Credit Institutions) in Bali serve as a container of wealth belonging to villages and villages in the form of money or other securities. It can be said that village credit institutions have an important role however, there are some cases of fraud that occur in village credit institutions in Bali that have a loss impact especially on the local village. Some research on fraud tendencies has been done but in this study will try to test the influence of accounting fraud tendencies seen from the Pentagon fraud and conducted at the village credit institution in Gianyar Regency. elements contained in the pentagon fraud: (1) Arrogance; (2) Competence/capability; (3) Leadership style (opportunity); (4) Locus of control (pressure); and (5) Rationalization. The population in this study at the village credit institute in Gianyar Regency with a sample of 75 respondents. From the test results using analysis methods PLS (Partial Least Square). obtained the result that the Effectiveness of Internal Control System has no effect on the tendency of accounting fraud in the Village Credit Institution Gianyar district and the effectiveness of technology-based Accounting Information System negatively affects the accounting fraud tendencies.